2012
DOI: 10.1590/s1676-06032012000400003
|View full text |Cite
|
Sign up to set email alerts
|

Morphological differentiation among migratory fish species from the Paraná River basin

Abstract: This study characterized the morphological differences among migratory fish species from the Paraná River Basin. A total of 177 adult fish of Leporinus elongatus, Leporinus macrocephalus, Prochilodus lineatus, Salminus brasiliensis, Pimelodus maculatus, Pinirampus pirinampu, Pseudoplatystoma corruscans, Pterodoras granulosus, and Rhaphiodon vulpinus were sampled in the Canal da Piracema, a fish passage system at Itaipu Dam, Paraná River. The migratory species were analyzed through 22 morphometric measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…Previous studies based on other river systems revealed significant links between fish morphology and their migration status, life history and functional groups [9]. In research conducted on the Pearl River in Southern China, the authors described changes in fish morphological traits along environmental gradients, while a remarkable association between morphometric variables and the migratory status of fish species was reported from Parana River Basin in Amazonia [10,11]. Reciprocally, in studies on Scandinavian lakes, the migratory behavior of freshwater fish was used as a predictor for fish morphological traits [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies based on other river systems revealed significant links between fish morphology and their migration status, life history and functional groups [9]. In research conducted on the Pearl River in Southern China, the authors described changes in fish morphological traits along environmental gradients, while a remarkable association between morphometric variables and the migratory status of fish species was reported from Parana River Basin in Amazonia [10,11]. Reciprocally, in studies on Scandinavian lakes, the migratory behavior of freshwater fish was used as a predictor for fish morphological traits [12].…”
Section: Introductionmentioning
confidence: 99%
“…Adicionalmente, a espécie ocorre na bacia do alto rio Paraná (Langeani et al, 2007;Pavanelli et al, 2007;Smith et al, 2007;Oliveira et al, 2010;Assumpção et al, 2012, Makrakis et al, 2007Britto & Carvalho, 2013), no baixo rio Mucuri, no estado de Minas Gerais (Pompeu & Martinez, 2007) e no rio Iguaçu (Agostinho et al, 2002;Baumgartner et al, 2012) no estado do Paraná, de forma alóctone, a partir de pisciculturas, de modo intencional ou acidental.…”
unclassified

Ficha de Leporinus macrocephalus

Carla Simone Pavanelli,
Fábio Vieira,
Priscila Camelier de Assis Cardoso
et al. 2024
Datasets - Sistema SALVE - ICMBio